(untitled) (BIRDEM Medical Journal, 2012)
Infertility is defined as failure to conceive during one year of unprotected frequent intercourse. Leading causes of infertility include tubal disease, ovulatory disorders, uterine or cervical factors, endometriosis and male factor infertility. A laparoscope is a thin fiber optic telescope that is inserted into the abdomen usually through the belly button. The fiber optics allow a light to used to see inside the abdomen. Carbon dioxide (CO2) gas is placed into the abdomen prior to inserting the laparoscope. Generally, laparoscopy should be reserved for couples who have already completed a more basic infertility evaluation including assessing for ovulation, ovarian reserve, ultrasound and hysterosalpingogram for the female and semen analysis for the male. Laparoscopy can help physicians diagnose many gynecological problems including endometriosis, uterine fibroids and other structural abnormalities, ovarian cysts, adhesions (scar tissue), and ectopic pregnancy. Robotic assisted laparoscopic surgery (RAL) is a more recent development and a form of operative laparoscopy. In RAL, the instruments and telescope are very similar to conventional laparoscopy, but they are attached to a robot which in turn is controlled by the surgeon who is seated at a viewing console. Women who have been diagnosed with endometriosis are more likely to experience infertility, and observational studies have shown that the monthly probability of pregnancy in women with endometriosis is about half of the probability in normal women. In spite of this well-documented association, a true cause and effect relationship has not been established. Laparoscopy is used world-wide to investigate infertility. It is an essential part of full assessment and treatment of infertility. It provides direct visualization of the pelvic organs, ovarian and tubal status and can elucidate the site of tubal obstruction. It has got an advantage of direct visualization of the pelvic organs and the peri-tubal status resulting in greater information as compared to hysterosalpingography and ultrasonography. The advance in instrument technology has made this procedure more productive and less hazardous. Laparoscopy is the most dependable tool to investigate pelvic pathology. The role of laparoscopy in diagnosis of infertility both primary as well as secondary is established beyond any doubt. DOI: http://dx.doi.org/10.3329/birdem.v2i2.12324 (Birdem Med J 2012; 2(2): 99-103)